THE INFLUENCE OF LEARNING FACILITIES ON SOCIAL SCIENCE LEARNING ACHIEVEMENT IN ELEMENTARY SCHOOL - Marsini (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to describe the effect of learning media on social science learning achievement in elementary schools. The purpose of managing educational facilities and infrastructure is to regulate and maintain educational facilities and infrastructure so that they can provide the best and meaningful contribution to the educational process, especially in the learning of Social Sciences (IPS). This research was conducted at Parang 5 Magetan Public Elementary School, East Java Province. The research uses qualitative research methods with data collectors such as document analysis, literature studies, interviews and observations. The results showed that inadequate facilities and infrastructure also occurred at SDN Parang 5, Magetan Regency, East Java Province, not a problem with access to difficult places, but seen from the condition of the school which only had 6 classrooms, no laboratory space (0), only 1 library room, 0 practice room, 0 leadership room, 0 administration room, 0 counseling room, 0 student council room and 0 prayer room. With the data on infrastructure facilities, it greatly influences social science learning achievement which is still low achievements and resulted in the accreditation of SDN Parang 5 is B.